Risk factors of severe fever with thrombocytopenia syndrome combined with central neurological complications: A five-year retrospective case–control study - Wang, Min; Huang, Peng; Liu, Wei; Tan, Weilong; Chen, Tianyan; Zeng, Tian; Zhu, Chuanlong; Shao, Jianguo; Xue, Hong; Li, Jun; Yue, Ming (Frontiers in Microbiology, 2022)
Objective Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease with high mortality rate, especially SFTS combined with central neurological complications. The purpose of this study was to explore risk factors of central neurological complications in SFTS patients. Methods In this retrospective study, SFTS patients admitted to the First Affiliated Hospital of Nanjing Medical University between January 2017 and December 2021 were enrolled. Based on the presence or absence of central neurological complications, SFTS patients were divided into case group and control group. The patients’ laboratory parameters and clinical data were collected for statistical analysis. Receiver operating characteristic (ROC) curve analysis was used to evaluate the prediction accuracy of independent risk factors in identifying SFTS patients with central neurological complications. Results In total, 198 hospitalized SFTS patients with complete medical records, clear etiological diagnosis and clinical outcomes were enrolled in this study. Of these, 74 (37.4%) cases were diagnosed with SFTS with central neurological complications, 29 (39.2%) cases died, and no death occurred in the control group. Multivariate logistic regression analysis revealed pulmonary rales, atrial fibrillation, and high serum SFTSV RNA, lactate dehydrogenase level during the fever stage as independent risk factors for the development of central neurological complications in SFTS patients. ROC curve analysis showed that the area under the ROC curve (AUC) of serum SFTSV RNA and lactate dehydrogenase levels were 0.748 (95%CI: 0.673–0.823, p < 0.001) and 0.864 (95%CI: 0.815–0.914, p < 0.001), respectively, in central neurological complications predicted in SFTS patients. Conclusion Severe fever with thrombocytopenia syndrome (SFTS) combined with central neurological complications has high morbidity and mortality and diverse clinical manifestations. Early monitoring of lung signs, electrocardiogram, blood SFTSV RNA, and lactate dehydrogenase levels in SFTS patients may be useful in predicting the occurrence of central neurological complications.